The Next Billion in Business: Women Entrepreneurs in Emerging Markets - Kothari, Tanvi; Roldan, Malu (Journal of Comparative International Management)

(untitled) (Management Futures, 2022)
Women-owned businesses are not only among the fastest-growing entrepreneurial ventures in the world but also have a significant impact on other women businesses and the economies at large. This paper uses an in-depth multiple-case study design to study twenty-two Women Entrepreneurs (WE) from diverse geographical, social, economic, and industrial sectors in two of the world’s fastest-growing emerging markets, India and the Philippines. The main message of our study is that in emerging markets, WEs ability to (simultaneously) sell products or offer solutions to niche segments and their capabilities to optimize resources by being innovative in identifying sources of funding, despite the institutional voids in emerging markets, enhances the competitive advantage of their businesses. To this extent, we introduce ‘A Framework to Explain the Paths of Building Women-Owned Businesses’ Competitive Advantage’ and identify some ‘propositions’ as anchors for further theory building. Finally, the findings of this study provide guidelines for entrepreneurs, educators, and policymakers that boosting women’s entrepreneurship and economic empowerment requires systemic solutions at scale.